Centring Aboriginal Worldviews in Social Work Education - Baskin, Cyndy (The Australian Journal of Indigenous Education, 2005)
Abstract As Aboriginal peoples gain more access to schools of social work, the academy needs to respond to their educational needs. This involves incorporating Aboriginal worldviews and research methodologies into social work education. This paper focuses on one definition of worldviews according to Aboriginal epistemology and implements an anti-colonial discursive framework in its analysis of education. It also critiques both the role of social work in the lives of Aboriginal peoples and the goals of social work education. Through the findings of a recent research project with Aboriginal social work students in Ontario, Canada, it raises key components that need to be addressed in the academy and provides ways in which this can be achieved. The overall theme flowing through this paper is that of decolonisation whereby reclamation of the belief that all peoples of the world have much to offer one another and life is a reciprocal process comes to the surface. In addition, the paper stresses the importance of this content being taught to all social work students and its relevance to all areas of Indigenous humanities.